2015
DOI: 10.1103/physrevb.91.235449
|View full text |Cite
|
Sign up to set email alerts
|

Tailored nanoantennas for directional Raman studies of individual carbon nanotubes

Abstract: We exploit the near field enhancement of nanoantennas to investigate the Raman spectra of otherwise not optically detectable carbon nanotubes (CNTs). We demonstrate that a top-down fabrication approach is particularly promising when applied to CNTs, owing to the sharp dependence of the scattered intensity on the angle between incident light polarization and CNT axis. In contrast to tip enhancement techniques, our method enables us to control the light polarization in the sample plane, locally amplifying and ro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…This is often the case: for a given laser frequency ω L , only a small fraction of the CNTs shows a significant signal. This is precisely where the advantage of optical antennas becomes obvious, as the signal amplification compensates for the suppression due to the energy mismatch [22]. As demonstrated in Fig.…”
Section: Figmentioning
confidence: 85%
See 4 more Smart Citations
“…This is often the case: for a given laser frequency ω L , only a small fraction of the CNTs shows a significant signal. This is precisely where the advantage of optical antennas becomes obvious, as the signal amplification compensates for the suppression due to the energy mismatch [22]. As demonstrated in Fig.…”
Section: Figmentioning
confidence: 85%
“…By following the standard assignment procedure we deduce the possible chiral indices for the CNT. We found that the most likely chiral indices are (22,5) or (21,7), two adjacent elements of the CNT family 2n + m = 49 which share very similar properties, as, e.g., diameter, chiral angle, and energy separation between VHSs [29,34].…”
Section: Figmentioning
confidence: 88%
See 3 more Smart Citations